Development of HOTS-Based Pocket Encyclopedia Books to Improve Science Literacy Culture in 21st-Century Learning - Sangadah, Siti; Zulfiati, Heri Maria; Nisa, Ana Fitrotun; Masjid, Akbar Al (FKIP Universitas Lampung, 2025)
The rapid development of information and communication technology has influenced the field of education, which can be utilized in the learning process. This study aims to test the feasibility and effectiveness of the development of HOTS-based pocket encyclopedia books in improving the culture of scientific literacy in 21st-century learning. This study is a research and development (R&D) with the Borg and Gall model. The subjects of this study consisted of 66 fifth-grade elementary school students in Klaten Regency, Central Java, who were selected using random sampling techniques. Data collection techniques through surveys, tests, and observations. Data was analyzed quantitatively by evaluating the category, and then analyzed qualitatively. The results of the study indicate that the development of HOTS-based pocket encyclopedia books is proven to be valid, feasible, and effective in improving the culture of scientific literacy in 21st-century learning. The non-parametric effectiveness test (Kruskal-Wallis test) shows a significance value of 0.445. This indicates that HOTS-based pocket encyclopedia books developed are effective in improving the culture of scientific literacy in 21st-century learning. The use of this learning media can be an innovative strategy in creating active, fun, and interesting learning. Keywords: pocket book, encyclopedia, high-order thinking skills, science literacy culture, science learning.